The Effect of Intellectual Capital on A Company's Performance Moderated by ITS Governance and IT Strategy Integration Employed By Bank Listed in Indonesian Stock Exchange - Irawanto, Dodi Wirawan; Gondomono, Haryo; Hussein, Ananda Sabil (The South East Asian Journal of Management, 2017)
This study investigates whether IT integration and company governance can affect the relationship between intellectual capital and company performance in the Indonesian banking sector. That could happen, as there are ever tighter and more numerous competitiveness levels in the banking sector, especially in the field of information technology (IT) and the support given by the top management. This study employs data from 33 banking companies listed on the ISE (Indonesian Stock Exchange) in 2013–2014. The testing was done on the elements of VAICTM (VACA, VAHU, STVA), moderated by IT strategy integration (ITSI) and corporate governance (DK) using the measurement of financial performance (ROA). The findings obtained show that VAHU has a positive effect on financial performance. If the VAICTM element were moderated by ITSI, then a well-integrated IT strategy would weaken the relationship between VACA and banking performance. The limitations of this study lie in the period of the data used, which is limited to 2013– 2014, and in that the component used for testing was done in isolation.